Chemical characterization of strawberry fruits in the organic and conventional cropping systems in pots / Caracterização química de frutos de morangueiro cultivados em vasos sob sistemas de manejo orgânico e convencional - Cristhiano Kopanski Camargo; Marcos Ventura Faria; João Eduardo Baier; Alexandre Gonçalves Galvão; Juliano Tadeu Vilela de Resende; Letícia Kurchaidt Pereira Camargo (Semina: Ciências Agrárias, 2009)
The nutritional quality of strawberry fruits of the cultivars Camarosa and Sweet Charlie cultivated in organic and conventional cropping systems was compared based on chemical characterization of the fruits by analyses of soluble solids content (SS), titratable acidity (AT), ratio (SS/AT), humidity, reducer sugars and total sugars. The experiment was performed in completely randomized blocks design, with four replications. There were differentiated effects of the cropping systems on the most of the evaluated traits and on the behavior of cultivars in each cropping system. The conventional cropping system was more effective in increasing contents of SS, AT and SS/AT in cultivar Sweet Charlie and the organic cropping system in cultivar Camarosa. The humidity in the conventional cropping system was significantly higher than that obtained from the organic cultivar Sweet Charlie. The percentages of total sugars in the conventional cropping system were statistically higher when compared with the organic for cultivar Sweet Charlie. It was verified a differentiated behavior of the cultivars in relation to the cropping system, for the most of evaluated traits. A qualidade nutricional de frutos de morango das cultivares Camarosa e Sweet Charlie, obtidos em sistemas orgânico e convencional, foi comparada com base na caracterização química dos frutos mediante análises dos teores de sólidos solúveis (SS), acidez titulável (AT), relação (SS/AT), umidade, açúcares redutores e açúcares totais. O delineamento experimental utilizado foi de blocos casualizados com quatro repetições. De modo geral foi observado efeito diferenciado dos tipos de sistemas de cultivo sobre a maioria das características e, principalmente, do comportamento das cultivares dentro de cada sistema. O sistema de produção convencional foi mais efetivo em aumentar os teores de SS, AT e SS/AT para a cultivar Sweet Charlie e o orgânico para a cultivar Camarosa. A umidade no sistema convencional foi significativamente superior ao orgânico para a cultivar Sweet Charlie. As porcentagens de açúcares totais no sistema convencional foram estatisticamente superiores quando comparadas ao orgânico, para a cultivar Sweet Charlie. Assim, verificou-se comportamento diferenciado das cultivares em relação ao sistema de cultivo, para a maioria das variáveis estudadas.